EVALUASI PELAKSANAAN PROGRAM NASIONAL AGRARIA DAN PENDAFTARAN TANAH SISTEMATIS LENGKAP DALAM PEMBANGUNAN WILAYAH DESA KINABUHUTAN, KECAMATAN LIKUPANG BARAT, KABUPATEN MINAHASA UTARA - Sherley Veralin Kamurahan; Bobby J. V. Polii; Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2018)
This study aims to evaluate the implementation of : (1) the national agrarian program certification (PRONA), and (2) complete systematic land registration (PTSL). The research used descriptive qualitative approach. This research was conducted in Kinabuhutan Village, West Likupang Sub-district, North Minahasa District, North Sulawesi Province, that conducted from June 2017 to January 2018. The sample consisted of 23 respondents for PRONA and 21 respondents for PTSL. Sample determination was done by using purposive sampling technique. Data collection methods used are Observation, Interview and Documentation. Data analysis technique used was descriptive qualitative. The results showed that: (1) Implementation of land certification through PRONA program has been run in accordance with the stages of activities determined according to regulations. However, there are problems in the implementation of: (i) proof of ownership (ownership rights) whether in the form of ownership based on sale and purchase or grant or inheritance, (ii) land tenure status as cultivator causing not knowing land history from first holder right until last owner and sign the upper limit of their land which is the main requirement in the management of the certificate. (2) The implementation of a Complete Systematic Soil System (PTSL) program is in accordance with the stages regulated. There are, however, shortcomings in which members of the community who have selected to participate in the PTSL program cannot show evidence for to proof of ownership, at the time of measurement there are not available at the site,and there is also no way of indicating the boundaries of the land because it has no boundary markers. The problem encountered in the implementation of both programs is the limited number of officers who have the competence as land measurement officers.